Esteroides produzidos por Penicillium herquei, um fungo endofítico isolado dos frutos de Melia azedarach (Meliaceae) - MARINHO, Andrey Moacir do Rosário (2009)
Six compounds comprising the groups of steroids, the ergosterol, the ergosterol peroxide, the cerevisterol, the neociclocitrinols, the ergosta-4,6,8(14),22-tetraen-3-one, the 25-hydroxy-ergosta-4,6,8(14),22-tetraen-3-one, were isolated from Penicillium herquei fungus obtained from Melia azedarach. The structures were identified by spectral methods of RMN 1D and 2D and MS.